Why Do Hens Pile? Hypothesizing the Causes and Consequences - Gray, Helen; Davies, Rachel; Bright, Ashleigh; Rayner, Ann; Asher, Lucy (Frontiers in Veterinary Science, 2020)
Piling is a behaviour in laying hens whereby individuals aggregate in larger numbers than would be normally expected. When piling behaviour leads to mortalities it is known as smothering and its frequent but unpredictable occurrence is a major concern for many egg producers. There are generally considered to be three types of piling: panic, nest box and recurring piling. Whilst nest box and panic piling have apparent triggers, recurring piling does not, making it an enigmatic and ethologically intriguing behaviour. The repetitive nature of recurring piling may result in a higher incidence of smothering and could have unconsidered, sub-lethal consequences. Here, we consider the possible causes of recurring piling from an ethological perspective and outline the potential welfare and production consequences. Drawing on a wide range of literature, we consider different timescales of causes from immediate triggers to ontogeny and domestication processes, and finally consider the evolution of collective behaviour. By considering different timescales of influence, we built four hypotheses relevant to the causes of piling, which state that the behaviour: i) is caused by hens moving towards or away from an attractant/repellent; ii) is socially influenced; iii) is influenced by early life experiences and; iv) can be described as a maladaptive collective behaviour. We further propose that the following could be welfare consequences of piling behaviour: Heat stress, physical injury (such as keel bone damage), and behavioural and physiological stress effects. Production consequences include direct and indirect mortality (smothering and knock-on effects of piling, respectively), potential negative impacts on egg quality and on worker welfare. In future studies the causes of piling and smothering should be considered according to the different timescales on which causes might occur. Here, both epidemiological and modelling approaches could support further study of piling behaviour, where empirical studies can be challenging.